Regional cooperation in South Asia (Bangladesh Institute of International and Strategic Studies, 2002)
Contributed articles presented at the International Conference on
Enth. 19 Beitr. - Includes bibliographical references
Keywords: Graue Literatur; Konferenzschrift; South Asian Association for Regional Cooperation; Congresses; Internationale Wirtschaftsbeziehungen; Regionale Wirtschaftsintegration; Internationale Zusammenarbeit; Südasien; SAARC-Staaten; ASEAN-Staaten; Internationale Sicherheit; South Asian cooperation